Dexamethasone release from hyaluronic acid microparticle and proanthocyanidin-gelatin hydrogel in sciatic tissue regeneration - Kazem Javanmardi; Hamideh Shahbazi; Ava Soltani Hekmat; Mehdi Khanmohammadi; Arash Goodarzi (Journal of Materials Science: Materials in Medicine)
Abstract Biodegradable microparticles are useful vehicles for the controlled release of bioactive molecules in drug delivery, tissue engineering and biopharmaceutical applications. We developed dexamethasone (Dex) encapsulation into tyramine-substituted hyaluronic acid microparticles (Dex-HA-Tyr Mp) mediated by horseradish peroxidase (HRP) crosslinking using a microfluidic device and infollowing crosslinked gelatin (Gela) with proanthocyanidin (PA) as a semi-confined bed hydrogel for the repair of sciatic tissue injury. It was found that the simultaneous use of Dex-HA-Tyr Mp and cross-linked Gela-PA hydrogel improved the physical properties of the hydrogel, including mechanical strength and degradability. The designed composite also provided a sustained release system for Dex delivery to the surrounding sites, demonstrating the applicability of the fabricated hydrogel composite for sciatic nerve tissue engineering and regeneration. The encapsulated cells were viable and showed adequate growth ability and morphogenesis during prolonged incubation in Gela-PA/HA-Tyr Mp hydrogel compared to control conditions. Interestingly, histological analysis revealed a significant increase in the number of axons in the injured sciatic nerve following treatment with Dex-HA-Tyr Mp and injectable Gela-PA hydrogel compared to other control groups. In conclusion, the results demonstrated that fabricated Dex-loaded MPs and injectable hydrogel from biomimetic components are suitable systems for sustained delivery of Dex with adequate biocompatibility and the approach may have potential therapeutic applications in peripheral nerve regeneration. Graphical Abstract